He should have told the bees : a novel - Cox, Amanda, 1984- (Revell, a division of Baker Publishing Group, 2023)
"Beekeeper Beckett Walsh is living her dream, working alongside her father in their apiary, until his untimely death sends her world into a tailspin. She suddenly finds she must deal with a new part owner of the family business--one who is looking to sell the property. Beck cannot fathom why her father would put her into the position to lose everything they built together. When Callie Peterson is named in the trust of a man she's never heard of, she's not sure what to do. Her fledgling business has just taken wing and her mother has reentered her life asking for help getting into rehab for her lifelong substance abuse issues, making Callie's financial situation rather . . . precarious. She's sure she has no right to someone else's farm, but the money from the sale could solve her problems and give her the stability she's always craved. As these two women navigate their present conundrum, they will discover a complex and entangled past full of secrets--and the potential for a brighter future for both of them" --